The Influence of Learning Motivation on Economic Learning Outcomes in Class X MAS PPMDH Medan Students in the 2023/2024 Academic Year - Samio, Samio; Rijal, Rijal; Hasibuan, Mhd Zulkifli; Dalyanto, Dalyanto (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
The purpose of this study was to improve moral activity and independence in learning Economics in class X students of MAS PPMDH Swasta Medan by looking at the influence of students' learning interests on the learning outcomes of Economics in the 2023/2024 Academic Year. This research is a quantitative study. The study was conducted by taking the learning outcomes of Economics for the Marketing material in the even semester of the 2023-2024 academic year and observing the influence of students' learning interests using an interest questionnaire consisting of 20 questions. The subjects of the study were students of class X A and class X B of MaS PPMDH Swasta Medan totaling 55 students. The data sources came from Economics subject teachers and student interest questionnaires. Data collection techniques were interest questionnaires and learning outcome tests. Data validity using the product moment correlation formula. Data analysis using normality tests, regression linearity tests, and determination tests. The research procedure used three stages, namely the preparation stage, the experiment implementation stage, the data analysis stage, and the report writing stage